2022
DOI: 10.1080/10717544.2022.2075986
|View full text |Cite
|
Sign up to set email alerts
|

Targeting interleukin-13 receptor α2 (IL-13Rα2) for glioblastoma therapy with surface functionalized nanocarriers

Abstract: Despite surgical and therapeutic advances, glioblastoma multiforme (GBM) is among the most fatal primary brain tumor that is aggressive in nature. Patients with GBM have a median lifespan of just 15 months when treated with the current standard of therapy, which includes surgical resection and concomitant chemo-radiotherapy. In recent years, nanotechnology has shown considerable promise in treating a variety of illnesses, and certain nanomaterials have been proven to pass the blood–brain barrier (BBB) and stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…Additionally, the absence of IL13Rα2 in the normal tissues surrounding GBM enhances its suitability as a target. Several approaches using peptide ligands to functionalize NPs have been employed to target this receptor . Gao et al modified the surface of docetaxel (DTX)-loaded lipid NPs with IL-13 peptide, proving its effectiveness as a ligand for IL-13Rα2 in treating GBM.…”
Section: Beyond the Surface: Peptide Functionalization Strategies For...mentioning
confidence: 99%
“…Additionally, the absence of IL13Rα2 in the normal tissues surrounding GBM enhances its suitability as a target. Several approaches using peptide ligands to functionalize NPs have been employed to target this receptor . Gao et al modified the surface of docetaxel (DTX)-loaded lipid NPs with IL-13 peptide, proving its effectiveness as a ligand for IL-13Rα2 in treating GBM.…”
Section: Beyond the Surface: Peptide Functionalization Strategies For...mentioning
confidence: 99%
“…One of the main interleukin receptors overexpressed in GBM is the IL13α 2 ​R receptor, being a promising candidate for GBM immunotherapy [ [178] , [179] , [180] ]. The Active Targeting Strategies of Nanocarriers for active targeting of interleukin are summarized in Table 4 .…”
Section: Receptor-mediator Targetingmentioning
confidence: 99%
“…; Table 2, Ref. [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]). It has been reported that blocking the activity of IL-6R by tocilizumab in a glioma cell line (U87MG) prevented cell proliferation by acting through the Janus kinase/signal transducer and activator of transcription 3 (JAK/STAT3) pathways [25].…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%
“…• Excess expression in GBM [56,57] • 70% of animal experiments that combined IL-13 with the toxin had long-term survival without discernible neurotoxicity • Actions on human GBM cells that are cytotoxic 11.…”
Section: Il-13mentioning
confidence: 99%